Separation and characterization of six (1 leads to 3)-beta-glucanases from Saccharomyces cerevisiae. - Hien, N H (1983)
Using a system of chromatography through columns of DEAE-Bio-Gel, HTP-Bio-Gel, and CM-Bio-Gel, we isolated and characterized six different (1 leads to 3)-beta-glucanases from cell wall autolysates and cell extracts of Saccharomyces cerevisiae haploid strain 2180B. These enzymes were designated glucanases I, II, IIIA, IIIB, IV, and V. The haploid mating type S. cerevisiae strain 2180A and the diploid strains S. cerevisiae 2180D and S. cerevisiae 595 contained the same complex of glucanases. Glucanases II and IIIA were exoenzymes, and glucanases I, IIIB, IV, and V were endoenzymes. The enzymes exhibited different molecular weights, kinetic properties, and activities on isolated yeast cell walls. The products of substrate (laminarin) hydrolysis were quantified by using high-pressure liquid chromatography and were significantly different for the four endoglucanases.